Jewish studies as counterlife: a report to the academy - Newton, Adam Zachary (Fordham University Press, 2019)
This book seeks to harness the possibilities offered by the evolving collection of forces by which Jewish Studies is constituted and practiced in order to open, refashion, and exemplify possibilities for a humanities to come.